2017
DOI: 10.1167/iovs.17-21769
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Inflammatory Biomarkers of Diabetic Retinopathy: An Integrative Approach

Abstract: Proinflammatory cytokines/chemokines play an essential role in the pathogenesis of DR. Therefore, circulating biomarkers and retinal imaging aimed at assessing inflammation have emerged as useful tools for monitoring the onset and progression of DR. In addition, "liquid biopsy" of AH seems a good option in patients with advanced stages of DR requiring intravitreous injections. This strategy may permit us to implement a more personalized treatment with better visual function outcome. Further evaluation and vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
3
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(116 citation statements)
references
References 93 publications
2
107
3
4
Order By: Relevance
“…First, aqueous humour is currently the most commonly used intraocular specimen for the study of retinal diseases, but vitreous fluid, as an index of primarily posterior segment pathology, should be considered the ideal sample in such cases. 14,40,41 However, aqueous sampling is less invasive than vitreous fluid sampling. Therefore, aqueous humour is considered the most appropriate biological sample for examining the intraocular biomarkers of DME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, aqueous humour is currently the most commonly used intraocular specimen for the study of retinal diseases, but vitreous fluid, as an index of primarily posterior segment pathology, should be considered the ideal sample in such cases. 14,40,41 However, aqueous sampling is less invasive than vitreous fluid sampling. Therefore, aqueous humour is considered the most appropriate biological sample for examining the intraocular biomarkers of DME.…”
Section: Discussionmentioning
confidence: 99%
“…13 Cellular events such as the increased expression of inflammatory mediators, leucostasis, and abnormal leukocyte adherence result in increased vascular permeability in the pathogenesis of DME. 14,15 It has been reported that the levels of VEGF, interleukin (IL)-6, IL-8, intercellular adhesion molecule-1 (ICAM-1), interferon gamma-induced protein-10 (IP-10), and monocyte chemoattractant protein-1 (MCP-1) are increased in DME patients compared with diabetic patients without DME. 16 However, the exact mechanisms and reasons for the response to anti-VEGF treatment in DME patients remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The main contributor to DME development has been thought to be the intraocular production of proinflam matory cytokines such as IL-6, IL-8, TNF-α, IL-1β, VEGF, pigment epithelium-derived factor, ICAM-1, and monocyte chemotactic protein (MCP-1) [9, 10, 24, 25]. There are very few data with regard to the altered levels of inflammatory mediators in peripheral blood of DME patients, in contrast to those mediators in intraocular blood [9, 11].…”
Section: Discussionmentioning
confidence: 99%
“…The generated reparative enzymes, formerly termed "heat shock proteins" that resulted from retinal pigment epithelium non-lethal laser heating that have thus far been measured include reductions in thiobarbituric acid reactive substances (TBARS), increased glutathione (GSH) and superoxide dismutase 1 (SOD1) as well as a reduction in cytochrome c, caspase 3 expression and activity along with cleaved caspase 9, and increased Beclin 1, p62, and LC3b (131). Reductions in markers of inflammation have also been documented in human diabetic retinopathy (132,133), and micropulsed laser treatment has been demonstrated to improved early forms of macular edema with significant improvement in vision and without evidence of laser injury (133)(134)(135). When the macular edema is more severe, however, similar to the studies of intravitreal anti-VEGF injections, the studies of micropulsed laser demonstrate only minimal improvement in the edema and in vision (presumably because of the already established, irreversible neurodegeneration) (11,133).…”
Section: Treatment/prevention Of Neurodegenerationmentioning
confidence: 99%